Evaluation of Antibiotics Appropriateness in the Treatment of Typhoid Fever in Pediatric Outpatient at Gondosari Gebog Kudus Health Center - Firda Tryana Yulistina (Universitas Negeri Semarang, 2022)
Background : Typhoid fever is an acute bacterial infection in the human digestive tract caused by Salmonella typhi bacteria. Typhoid fever is treated with antibiotics. However, inappropriate use of antibiotics can lead to resistance. Aim : To evaluate the appropriateness of using antibiotics in outpatient pediatric typhoid fever at the Gondosari Gebog Kudus Health Center in 2021-2022. Methods : Non-experimental research with retrospective data collection and descriptive analysis. Parameters in this study for evaluating the antibiotics appropriateness are 7 parameters (right diagnosis, right patient, right indication, right drug, right dose, right way of administration, and right duration) based on the Rational Drug Use module according to Indonesian Ministry of Health (2011). Results : The samples obtained in this study were 40 patients. The results of evaluating the appropriate use of antibiotics in pediatric typhoid fever in this study were 100% right diagnosis, 100% right patient, 100% right indication, 100% right drug according to WHO (2011), 100% right drug according to Indonesian Ministry of Health (2006), 85% right dose according to WHO (2011), 100% right dose according to Indonesian Ministry of Health (2006), 100% right method of administration, 20% right duration according to WHO (2011), and 80% right duration according to Indonesian Ministry of Health (2006). Conclusion : The results of the evaluation of the appropriate use of antibiotics at the Gondosari Health Center are appropriate based on 7 parameters (right diagnosis, right patient, right indication, right drug, right dose, right way of administration, and right duration). Keywords : Typhoid fever, Antibiotics, Appropriateness of treatment